(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
in this article, the lexicon of pottery was considered on the example of Khorezm dialect. Words related to the field of pottery in the folk language, which have been engaged in this field since ancient times, were analyzed. The work done so far in this regard is studied.